The Relationship Of Interest In Entrepreneurship With Student's Learning Motivation In Entrepreneurship Creative Products At Smk N 1 Lubuk Sikaping - Putri, Ella Dwi; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research is motivated by the presence of some students who do not realize that increasing student motivation in the subject of creative entrepreneurship products can generate students' interest in entrepreneurship. The purpose of this study was to determine the relationship between interest in entrepreneurship and learning motivation of class XI students in the subject of creative entrepreneurship products at SMK N 1 Lubuk Sikaping. This type of research is quantitative with a correlational approach. The population in this study was class XI students at the State Vocational High School (SMK N) 1 Lubuk Attitude, totaling 471 students. The sample in this study was taken using a proportional random sampling technique totaling 82 students of class XI. Data collection techniques were measured using a Likert scale. The data analysis used is descriptive and correlation analysis. The results showed that the interest in entrepreneurship has a positive and significant relationship with the learning motivation of Class XI students in the subject of creative entrepreneurship products at SMK N 1 Lubuk Attitude with a medium category of 0.511. The level of achievement of respondents in entrepreneurship interest and student motivation in the subject of creative entrepreneurship products is in the high category. Based on this data, it can be said that the interest in entrepreneurship and learning motivation of class XI students in the subject of creative entrepreneurship products at SMK N 1 Lubuk Sikaping is generally high.